Ethanolic Extract of Capparis cartilaginea Decne as an Ameliorative Agent Against CCl4 Induced Testicular Damage in Male Albino Rats - Al-Shaibani, Elham A.S.; Al-Hamdani, Nada M.H.; Al-Khatib, Bushra Y.H.; Almansory, Anisa H.; Masood, Anwar M.A.; Ibrahim, Hassan M. (PSM Biological Research, 2025)
Capparis cartilaginea Decne. (Capparaceae) has been traditionally used for various therapeutic purposes. This study aimed to evaluate the ameliorative effect of C. cartilaginea ethanolic leaf extract on testicular damage induced by carbon tetrachloride (CCl?) in rats. Twenty-five adult male albino rats, weighing between 130 and 180 g, were randomly divided into five groups. Group I (Control) received no treatment - Group TI was administered olive oil (0.5 ml orally) as a vehicle control - Group TII received the ethanolic leaf extract of C. cartilaginea at a dose of 500 mg/kg orally - Group TIII was treated with carbon tetrachloride (CCl?) at a dose of 2 mg/kg, administered intraperitoneally on alternate days to induce testicular toxicity - Group TIV received CCl? (2 mg/kg intraperitoneally on alternate days) followed by ethanolic extract (500 mg/kg orally). At the end of the experiment, all rats were sacrificed and testes were collected for histopathological analysis. The CCl? treated group exhibited a significant reduction in both body weight and relative testicular weight, along with causing fibrosis, congestion, interstitial edema, and degeneration of the seminiferous tubules. In contrast, the control, TI, and all C. cartilaginea-treated groups, including TIV, which received CCl? followed by the ethanolic extract, preserved normal testicular architecture, similar to that of the control group.. These results suggest that the ethanolic leaf extract of C. cartilaginea offers a restorative effect against CCl? induced testicular toxicity in rats.